Whence-a-Word?: An Eye for an Eye - Dospěl, Marek (The Biblical archaeology review, 2025)
The phrase "an eye for an eye" describes a type of retributive justice. Known in legal circles as lex talionis, or "the law of retaliation," it stipulates that a punishment or compensation be commensurate with the crime committed or damage caused. The expression entered our parlance through the Hebrew Bible, where this principle of natural […]